PENGEMBANGAN MANAJEMEN USAHA HOME INDUSTRI DI MANUKAN (TENGGER KANDANGAN) KECAMATAN BENOWO KOTA SURABAYA - Ignatia Martha Hendrati; Nuruni Ika Kusuma Wardani; Kiky Asmara (Universitas Pahlawan Tuanku Tambusai, 2022)
The Bread Bolu Roll business has been very promising for those who are involved in it, because bread is a delicious and filling snack. In addition to these two factors, bread Bolu Gulung also has many enthusiasts of all ages and various backgrounds. if you look at the competitors who are engaged in the same business, there are already quite a lot. with better taste innovations, beautiful and attractive sizes, economical prices, and most importantly healthy and hygienic by providing attractive packaging and labels so that partner products are able to compete and sell well in the market. home Industry Sponge Bread Rolls Tengger Kandangan District Benowo Surabayadoes not yet have regular customers, so it will increase its marketing by making attractive packaging and labels to find markets and even agents who want to sell it, so there will be many who help to develop the bread Bolu businessSteamed Rolls.The problems faced are (1) the entrepreneurial management has not been maximally carried out (2) has not been given good packaging on the products and (3) has not been given labeling to introduce their products. Keywords: bussines mangement, packaging , labelling